Deleneation of Landslide Prone Zones of Nepal - Paudyal, Arun Sharma; Mathur, H. N. (Indian Forester, 1985)
An attempt has been made in this paper to deleneate landslide prone zones of Nepal - a mountaneous Himalayan Kingdom plagued with landslide menace. The landslide Atlas of Nepal has been prepared by super imposing the lithological erodibility map of Nepal and locating the existing major landslide, on the ecological zones map of Nepal. The country has been divided into four landslide prone zooes in order of susceptibility. The landslide Atlas of Nepal can assist in containing the landslide menace.